PECULIARITIES OF DETENTION OF PERSONS WANTED ON A CRIMINAL CASE BEING AT THE STAGE OF TRIAL ACCORDING TO CRIMINAL PROCEDURE CODE OF RA - Melikyan, Gayane (State and Law, 2022)
The article is devoted to the peculiarities of the detention of persons wanted by a foreign state under the Criminal Procedure Code of the Republic of Armenia. The article examines the subjects having the right to file a petition for detention, the documents required for the petition, etc. The article also examines the issues arising in practice in connection with the subject composition of the submission of the relevant petition, and the proposals are suggested for the corresponding amendments to be included in the Criminal Procedure Code of the Republic of Armenia. Keywords: temporary detention, detention with the purpose of extradition, the Prosecutor, the RA Ministry of Justice, etc.